The Microstructure Behavior of SGX Nikkei 225 Index Futures Resulting from Component Changes of the Underlying Cash Market Index - CHAROENWONG, Charlie (Institutional Knowledge at Singapore Management University, 2016)
We study the effect of changes involving component stocks of the Nikkei 225 stock index on the behavior of the Nikkei 225 index futures. Specifically, we examine the effects of component changes of the Nikkei 225 on the volume, returns, volatility, and bid-ask spreads (BAS) on its corresponding futures contract traded on the Singapore Exchange (SGX). We find that trading volume increases and the bid-ask spread decreases but there is no significant change in the returns of the SGX Nikkei 225 index futures after a component change takes place. This does not support the Price Pressure Hypothesis, which states that the increase in price of a stock after it is newly added into a stock index is only temporary and gradually reverts (Vespro, 2006; Harris and Gurel, 1986; Lynch and Mendenhall, 1997). We find weak evidence that volatility decreases, contrary to the findings of Vespro (2006) and Lynch and Mendenhall (1997).